Development of android application: Islamic learning for children / Nik Nor Nabila Nik Ismail - Nik Ismail, Nik Nor Nabila (2014)
Islamic Learning for Children is an Android Application development for children aged between 10 to 12 years old. This application tends to give benefits for children to learn series of dua and stories of the prophets acutely. Existing application for dua and stories of prophets currently are not integrated. The objectives of this research are to identify the requirements for Islamic Learning for Children on Android application, to design Islamic Learning for Children on Android application and to develop Islamic Learning for Children on Android platform. Nowadays, children in early ages already know how to used smartphones, tablets and others that related to Android. Children can learn comprehensively through the application with a series dua and stories of the prophets which are a good start for them to learn in their early ages. The application is developed using Adobe Flash Professional CS6. The methodology used is ADDIE model which consists of 5 phases, this project only focuses on four phases which are analysis, design, development and implementation. From the analysis of questionnaire, it shows that 62.9% of respondents preferred to learn through m-learning while 30.8% of them refused. It also shows types of m-learning preferred by respondents which 24.1% prefer stories, 31.3% prefer sound, 39.4% prefer both stories and sound and 5.2% prefer others such as videos and quizzes. For the future work, developer can use other platforms such as iOS and Windows for Islamic Learning for Children. This research has achieved its three main objectives.